2023
DOI: 10.3389/fendo.2023.1239502
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetically predicted sex and growth hormones and facial aging in the UK Biobank: a two−sample Mendelian randomization study

Mingjian Zhao,
Huiyun Lv,
Yunshu Zhang
et al.

Abstract: BackgroundAging is an inescapable process, but it can be slowed down, particularly facial aging. Sex and growth hormones have been shown to play an important role in the process of facial aging. We investigated this association further, using a two-sample Mendelian randomization study.MethodsWe analyzed genome-wide association study (GWAS) data from the UK Biobank database comprising facial aging data from 432,999 samples, using two-sample Mendelian randomization. In addition, single-nucleotide polymorphism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Besides, the anti-ageing effect of sex hormones, especially testosterone, also has been reported, indicating its potential role in improving ageing-related disease [20]. Declined testosterone levels is one of the most characters of ageing due to their associated with genetic predispositions, increased body fat, and disease [21,22]. Many studies have shown that sex hormone levels are associated with cardiovascular calci cation, but most of them focus on coronary artery calci cation [23][24][25][26].…”
mentioning
confidence: 99%
“…Besides, the anti-ageing effect of sex hormones, especially testosterone, also has been reported, indicating its potential role in improving ageing-related disease [20]. Declined testosterone levels is one of the most characters of ageing due to their associated with genetic predispositions, increased body fat, and disease [21,22]. Many studies have shown that sex hormone levels are associated with cardiovascular calci cation, but most of them focus on coronary artery calci cation [23][24][25][26].…”
mentioning
confidence: 99%